A Study on The Determinants of Singapore Polytechnic Students’ Choices in A Hospitality and Tourism Program - Justin Matthew Pang (Centre For Tourism Planning and Development, 2020)
The hospitality and tourism industry in Singapore is rapidly growing and all polytechnics in Singapore are offering hospitality courses so that they can help sustain the economy with the necessary manpower. However, the new generation of Singapore millennial students choosing hospitality programs assess choice factors differently and give different priorities of importance to these factors. Factors have been grouped according to ‘Personal’, ‘Institution – Academic’, ‘Institution – Others’, and ‘Curriculum’, and students rated these on their own perceptions and against those perceptions from the faculty when designing hospitality programs to attract potential students. It has been noted that the ability to get a job after graduation is of the highest importance to both parties and that parents' and peers' influence do not matter in their choice of hospitality programs or polytechnics. With this understanding, educational institutions would need to relook at their strategies for enticing students to join their programs. This study will also grant a precursory insight into how students from developing Asian countries will select hospitality programs, using Singapore as a model in the future.